2017
DOI: 10.1016/j.omtm.2017.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the Virion Host Shut-off Gene Enhances Neuronal-Selective Transgene Expression from an HSV Vector Lacking Functional IE Genes

Abstract: The ability of herpes simplex virus (HSV) to establish lifelong latency in neurons suggests that HSV-derived vectors hold promise for gene delivery to the nervous system. However, vector toxicity and transgene silencing have created significant barriers to vector applications to the brain. Recently, we described a vector defective for all immediate-early gene expression and deleted for the joint region between the two unique genome segments that proved capable of extended transgene expression in non-neuronal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…In contrast, very little, if any, EGFP signal was detected at any time point. These results indicated that A2UCOE can enhance transient, independent expression of a second transgene in the central nervous system to complement the previously described durable expression of a first transgene positioned in the deleted ICP4 locus (31,32). It remains to be determined what mechanisms can account for the rapid or immediate silencing of the LAT-based EGFP cassette of these vectors in mouse hippocampus.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…In contrast, very little, if any, EGFP signal was detected at any time point. These results indicated that A2UCOE can enhance transient, independent expression of a second transgene in the central nervous system to complement the previously described durable expression of a first transgene positioned in the deleted ICP4 locus (31,32). It remains to be determined what mechanisms can account for the rapid or immediate silencing of the LAT-based EGFP cassette of these vectors in mouse hippocampus.…”
Section: Resultssupporting
confidence: 54%
“…We hypothesize that the unexpected long-term reporter gene expression from the terminal ICP4 locus of our defective vectors in central nervous system neurons in vivo (Fig. 9C) (31,32) and the simultaneous lack of reporter expression from the LAT locus reported here are consequences of the disruption of CTCF interactions and the loss of LAT and ICP0 functions. However, it is uncertain whether A2UCOE activity is influenced by the same mechanisms.…”
Section: Discussionmentioning
confidence: 79%
“…Our studies demonstrated prolonged, non-toxic transgene expression from a foreign promoter inserted directly downstream from the LAT promoter/enhancer region in non-neuronal cells. Interestingly, although expression from the LAT region was transient in rDRG cultures and largely undetectable in mouse hippocampus [ 104 , 105 ], reporter expression from the deleted ICP4 locus without adjacent LAT regulatory elements persisted for months in mouse hippocampus [ 106 ]. Furthermore, we observed that this expression could be further enhanced by deletion of the virion host shutoff gene (vhs or UL41) [ 104 ].…”
Section: Replication-defective Hsv Vectorsmentioning
confidence: 99%
“…Interestingly, although expression from the LAT region was transient in rDRG cultures and largely undetectable in mouse hippocampus [ 104 , 105 ], reporter expression from the deleted ICP4 locus without adjacent LAT regulatory elements persisted for months in mouse hippocampus [ 106 ]. Furthermore, we observed that this expression could be further enhanced by deletion of the virion host shutoff gene (vhs or UL41) [ 104 ]. Studies by Harkness et al [ 107 ], using their IE-inactive d 109 vector, showed that genes near or within the long viral inverted repeat regions remained more active than genes in the unique regions of the largely quiescent genome in cultured trigeminal ganglion neurons.…”
Section: Replication-defective Hsv Vectorsmentioning
confidence: 99%
See 1 more Smart Citation